Effect of Organic Linkers on Metal-Organic Frameworks Electrode Fabrication for Battery Supercapacitor Hybrid Application - Amir Luqman, Sanusi; Nurul Khairiyyah, Mohd Zain; Izan Izwan, Misnon; Rajan, Jose (Trans Tech Publications, 2021)
Metal organic framework (MOFs) of ternary metal precursors with different organic linkers are synthesized and fabricated on Ni-foam as the electrodes via hydrothermal reaction aiming to enhance the electrical conductivity and the specific capacitance, Cs. We report the preparation of ternary metal with different organic linkers named CoCuNi-bi using terephthalic acid (H2bdc), CoCuNi-tri using trimellitic acid and CoCuNi-tetra using pyromellitic acid with increasing of active sites on Ni-foam substrate respectively. The CoCuNi-tetra demonstrates the highest Cs of 740 F g-1 at 2 mV/s & 791 F g-1 (87.9 mAh g-1) at 1 Ag-1 respectively followed by CoCuNi-tri (674 F g-1 at 1 A g-1; 74.9 mAh g-1) and CoCuNi-bi (591 F g-1 at 1 A g-1; 65.7 mAh g-1). CoCuNi-tetra shows the best electrochemical performance hence it could be the encouraging electrode for supercapacitor materials.